Art in the Muhammadiyah Islamic View: A Balance of Aesthetics and Ethics - Hanama, Akhmad; Siswanto, Deny Hadi (Asian Journal of Philosophy and Religion, 2025)
Art plays a crucial role in human life, reflecting social, cultural, and religious values. This study examines the concept of art according to Islamic scholars, the Qur'an, and Hadith, as well as the Muhammadiyah perspective. The approach used is literature review. The findings reveal that art in Islam has aesthetic, moral, and spiritual dimensions, serving not only as a visual expression of beauty but also as a means of drawing closer to Allah and improving character. Islamic scholars stress that art must align with sharia, carrying spiritual value and fulfilling religious obligations. Muhammadiyah’s view of art emphasizes the balance of aesthetics and ethics, aiming to educate, improve character, and strengthen faith without contradicting sharia.